Short-term sedimentation dynamics in mesotidal marshes - Carrasco, Rita (2023)
One of the key questions about wetlands resilience to sea-level rise is whether sediment supply will be enough to keep them coping with growing inundation levels. To address this question, researchers have put a lot of effort into field data collection and ecogeomorphic modelling, in an attempt to identify the tipping points of marsh survival. This study uses fieldwork data to characterize the sediment fluxes between the tidal flats and salt marshes, in the Ria Formosa lagoon (Portugal). Sediment fluxes were measured from the tidal channel towards the mid-upper marsh, during neap and spring tide conditions. The flow magnitude was measured, and induced transport was determined based on shear velocities. Deposition rates, instantaneous suspended sediment and near-bed velocities were linked through theoretical formulas and used to characterize time-averaged conditions for sediment delivery and deposition to the site. The results showed that suspended sediment concentrations and sediment deposition varied across the transect with no specific relation to elevation. Maximum water depths were recorded in the vegetated tidal flat, and the maximum currents were flood dominated, in the order of 0.20 m/s, in the low marsh due to flow-plant interactions and an increase of turbulence. Deposition rates ranged between 20 to 45 g/m(2)/hr, after a complete tidal cycle, and were higher in the mid-upper marsh. Hydroperiod was not the main contributor to sediment deposition in the study area. Sediment transport was tidally driven, strongly two-dimension during the cycle, and highly influenced by the vegetation. Measurements of marsh sediment flux obtained in our work are diverse from the ones found in the literature and evidence the importance of considering spatio-temporal variability of vegetated platforms in assessing overall marsh bed level changes.